Appropriate Personality of Teaching Profession among Industrial Education Students of King Mongkut's Institute of Technology Ladkrabang - Ratchadakorn Phonpakdee (My University, 2014)
The research study determined the Appropriate Personality of Teaching Profession (APTP) strategies and their development in students of the Faculty of Industrial Education (IdEd). A total of 354 students and 24 lecturers were identified as respondents to provide pertinent data. The research methods used were interviews, APTP evaluation test, and checklist of questions. Data were statistically interpreted and analyzed using frequency counts, percentage, mean, and standard deviation. Results reveal that most of the students adhere to more APTP dimensions particularly on psychological personality, physical appearance, emotions, verbal communication, and intellect. Both lecturers and students mostly agreed on the 5 dimensions to be developed through APTP.
Keywords: Intellect; Education and Communication Studies